Indonesia Cohort of IO HAT Study to Evaluate Diabetes Management, Control, and Complications in Retrospective and Prospective Periods Among Insulin-Treated Patients with Type 1 and Type 2 Diabetes - Achmad Rudijanto; Made R Saraswati; Em Yunir; Poppy Kumala; Happy HS Puteri; Veny VV Mandang (Acta Medica Indonesiana, 2018)
Background: hypoglycemia is a major adverse event of insulin therapy for diabetes mellitus patients. The study was conducted to evaluate the incidence of hypoglycemia among insulin treated patients with type 1 diabetes mellitus (T1DM) or type 2 diabetes mellitus (T2DM) in the Indonesian cohort. Methods: this Indonesian cohort study consisted of retrospective and prospective evaluation of hypoglycemic episodes, using International Operations Hypoglycemia Assessment Tool (IO HAT) in 374 patients with diabetes (T1DM; n=17 or T2DM; n=357). The patients of ≥18 years of age and treated with insulin for >12 months were selected for this study (ClinicalTrials.gov number: NCT02306681). Results: a total of 374 patients were enrolled in this study and completed SAQ1. All patients with T1DM (17 [100%]), and 347 (97.2%) patients with T2DM completed SAQ2. Almost all the patients in the 4-week prospective period reported at least one hypoglycemic event (T1DM 100%, T2DM 99.4%) and the incidence rate of any hypoglycemia was 67.5 events per patient-year (PPY) and 25.7 events PPY for T1DM and T2DM patients, respectively. Among patients with T1DM and T2DM, 5.9% and 36.4%, respectively, did not know what hypoglycemia was at baseline, also high proportion of patients had impaired hypoglycemic awareness in the study (82.4% and 62.7%, respectively). Conclusion: overall, high proportion of patients reported hypoglycemic events in the prospective period indicating under reporting during the retrospective period due to recall bias. Therefore, there is a need for patient education program to improve the awareness of hypoglycemia in diabetes patient in Indonesia.